PENGEMBANGAN WORK-RELATED POSITIVE AND NEGATIVE AFFECT SCHEDULE PADA PEKERJA GENERASI Z - Widya Sasi Maheswari; Heryanna Wijaya; Kadek Erinna Chandra Wijaya; Servia; Rita Markus Idulfilastri; Celine Yovita (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT This study aims to develop a contextual Work-Related Positive and Negative Affect Schedule (W-PANAS) instrument for Generation Z employees to measure emotional experiences in the workplace. The background of this research is based on the distinctive emotional dynamics and work-related stress patterns of Generation Z, which require a more contextually relevant affect measurement tool aligned with modern work environments. This study employed a quantitative approach with a cross-sectional design. The participants consisted of 302 Generation Z workers aged 18–29 years with a minimum of six months of work experience. The developed instrument included 20 items, consisting of 10 positive affect items and 10 negative affect items, measured using a 5-point Likert scale. Data analysis was conducted through item validity testing, reliability testing, and Confirmatory Factor Analysis (CFA) to examine the construct structure of the instrument. The results indicate that the W-PANAS demonstrates good validity and reliability and successfully represents two main affect dimensions, namely positive affect and negative affect in the work context. Therefore, the W-PANAS is considered an appropriate and contextually relevant instrument for assessing the emotional experiences of Generation Z employees in the workplace. ABSTRAK Penelitian ini bertujuan untuk mengembangkan instrumen Work-Related Positive and Negative Affect Schedule (W-PANAS) yang kontekstual bagi pekerja Generasi Z dalam mengukur pengalaman emosional di lingkungan kerja. Latar belakang penelitian ini didasarkan pada karakteristik Generasi Z yang memiliki dinamika emosional dan tingkat stres kerja yang khas, sehingga memerlukan instrumen pengukuran afek yang lebih relevan dengan konteks pekerjaan modern. Penelitian ini menggunakan pendekatan kuantitatif dengan desain cross-sectional. Partisipan terdiri dari 302 pekerja Generasi Z berusia 18–29 tahun dengan masa kerja minimal enam bulan. Instrumen yang dikembangkan berjumlah 20 butir pernyataan yang terdiri atas 10 item afek positif dan 10 item afek negatif dengan skala Likert 1–5. Proses analisis data dilakukan melalui uji validitas butir, uji reliabilitas, serta analisis faktor konfirmatori (Confirmatory Factor Analysis/CFA) untuk menguji struktur konstruk instrumen. Hasil penelitian menunjukkan bahwa W-PANAS memiliki tingkat validitas dan reliabilitas yang baik serta mampu merepresentasikan dua dimensi utama afek, yaitu afek positif dan afek negatif dalam konteks kerja. Dengan demikian, W-PANAS dinyatakan layak digunakan sebagai instrumen pengukuran pengalaman emosional pekerja Generasi Z di lingkungan kerja secara lebih kontekstual dan relevan.